COMPARATIVE CHARACTERISTICS OF ANTIOXIDANTS AT THE EXPERIMENTAL PORPHYRIN EXCHANGE - Kryzhna, S.I.; Sakharova, T.V. (World of Medicine and Biology, 2012)
There are shown the results of studies the parameters of heme metabolism and the proven occurrence of toxic liver injury due to experimental porphyrin exchange. These changes were characterized by increased concentrations of ALA and PBG, an increase in activity in rat plasma indicators of cytolysis, cholestasis and parenchymal inflammation. It is established that the use of antioxidants significantly improved state of the disease as indicators of ALA and PBG, as well as on indicators of cytolytic activity of blood plasma. However, the most active among the studied drugs is showed the preductal. It is proved that due to of acute hepatitis preductal has the greatest corrective impact on the activity of cytolytic enzymes and thymol.